Strategic entrepreneurship, competitive advantage, and SMEs' performance in the welding industry in Tanzania - Kibeshi Kiyabo; Nsubili Isaga (Journal of Global Entrepreneurship Research, 2019)
This study aimed at obtaining empirical evidence regarding the influence of strategic entrepreneurship on SMEs' performance under the mediation of competitive advantage in the welding industry in Tanzania. Guided by the resource-based theory, this study adopted learning orientation, strategic resource management, and entrepreneurial orientation as strategic entrepreneurship components. Survey method with cross-sectional design was used to collect data from 300 owners-managers of welding industry SMEs located in Dar es Salaam, Morogoro, and Mbeya urban centers. Structural equation modelling technique was used to develop measurement and structural models. Findings suggest that learning orientation influences entrepreneurial orientation which influences strategic resource management to create competitive advantage that promotes SMEs' performance. Findings of this study imply that the resource-based theory holds a better chance to describe the influence of strategic entrepreneurship components on SMEs' performance under the mediation of competitive advantage than the individual resource-based view and knowledge-based view. It has been empirically demonstrated that knowledge is a unique resource that enables the acquisition of other resources and strategies. SMEs are urged to embrace learning orientation to create competitive advantage that leads to superior performance. The study has empirically verified that learning orientation, strategic resource management, and entrepreneurial orientation constructs adopted from entrepreneurship and strategic management literature are components of strategic entrepreneurship. Inclusion of strategic entrepreneurship components, competitive advantage, and SMEs' performance with their composite measures in a single model distinguishes this study from past studies.
Keywords: 650; Competitive advantage; SMEs' performance; Strategic entrepreneurship; Tanzania; Welding industry